2012
DOI: 10.4319/lo.2012.57.5.1427
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic events stimulate nitrogen recycling in a shallow salt‐wedge estuary: The Yarra River estuary, Australia

Abstract: The Yarra River estuary is a salt-wedge estuary prone to periods of stratification-induced anoxia and hypoxia (O 2 , 100 mmol L 21 ) during low-flow events. Nitrate reduction pathways were examined using the 15 N isotope pairing technique in intact sediment cores, emulating in situ conditions, to evaluate the fate of NO Whole-system estimates using deviations from conservative behavior and core incubations were in good agreement and showed that NH z 4 was regenerated more efficiently relative to DIC under hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 48 publications
6
73
2
Order By: Relevance
“…When observed, DNRA occurred at relatively high bottomwater NO 3 − concentrations for this study, ranging from 1.87 to 10.9 μM. This observation supports work in Australia, where low NO 3 − inhibited DNRA during hypoxia (Roberts et al 2012). DNRA is often associated with sulfur cycling (e.g., Brunet and Garcia-Gil 1996), and H 2 S was observed in a parallel microelectrode study in May 2010 (K.S.…”
Section: Anammox Dnra and N Fixationsupporting
confidence: 87%
“…When observed, DNRA occurred at relatively high bottomwater NO 3 − concentrations for this study, ranging from 1.87 to 10.9 μM. This observation supports work in Australia, where low NO 3 − inhibited DNRA during hypoxia (Roberts et al 2012). DNRA is often associated with sulfur cycling (e.g., Brunet and Garcia-Gil 1996), and H 2 S was observed in a parallel microelectrode study in May 2010 (K.S.…”
Section: Anammox Dnra and N Fixationsupporting
confidence: 87%
“…3: Dale et al 2011;Roberts et al 2012Roberts et al , 2014Behrendt et al 2013;Bonaglia et al 2014a). Several environmental factors have been shown to govern the relative importance of DNRA and denitrification in marine and estuarine sediments, among which are temperature, sediment oxygen dynamics, salinity, presence of benthic microalgae (summarized in Giblin et al 2013), nitrate concentration (Roberts et al 2012) and Fe 2? availability (Roberts et al 2014).…”
Section: Regulation Of Nitrate Reduction In Newly Oxidized Sedimentsmentioning
confidence: 99%
“…Conley et al 2002;Viktorsson et al 2012Viktorsson et al , 2013Stigebrandt et al 2014). Hall et al 1992;Dale et al 2011;Roberts et al 2012), but these differ from permanently anoxic systems because of the survival of some bioturbating fauna. If nitrate diffuses into an oxygen depleted environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increases in NH 4 efflux could also be associated with the stimulation of dissimilatory reduction of nitrate to ammonium (DNRA) (Silver et al, 2001). Although DNRA is thought to occur only in highly reducing environments capable of maintaining sustained anaerobic metabolism (Tiedje, 1988) and does not normally play an important quantitative role in oxygenated estuarine sediments (Binnerup et al, 1992;Christensen et al, 2000;Gilbert et al, 1997) a recent study has shown that DNRA does occur in oxygenated sediment (Roberts et al, 2012).…”
Section: Discussionmentioning
confidence: 97%